#TITLE_ALTERNATIVE# - (NIM 322 95 034), Salama
ABSTRACT: Silicone elastomer is a synthetic polymer. Its usage as an outdoor polymeric insulator for high/extra high voltage electrical lines is relative new. It has some advantages compared to that of conventional materials such as porcelain, ceramics and glasses that have long been used. The advantages are in its lighter weight, better dielectric properties, volume resistance, thermal properties, mechanical strength, resistant to earthquake and easier to maintain than the conventional ones. The silicone elastomer has advantageous features that make it more favorable as an insulator material than porcelain and glasses or other polymers. The good features are on its hydrophobicity and ability to induce hidrophobicity to pollutants attached on insulators surface. This phenomenon is called as hydrophobicity transfer. The hydrophobicity and its ability to transfer it to pollutant layers are very useful in outdoor insulator because in moist, wet or rain condition it prevents the formation of continuous water layer so that low conductivity of insulator may be maintained. The chemical structure of silicone elastomer consists of backbone bonds of inorganic substances (silicone and oxygen) that are resistant to aging, and side bond of organic substances (carbon and hydrogen) that can be degraded by climate factors as high temperature, moisture or rain and high intensity of uv radiation in tropical area as Indonesia. The tropical climate stresses might change the properties of silicone elastomer that are indicated by changes of color, increase of dielectric properties, lose of hydrophobicity, increase of leakage current, and occurrence of tracking and erosion that shortening its age. Researchers are continually searching for vulcanization method, type and threshold of filler that can improve the performance of silicone elastomer in certain condition. High dose of filler in the insulator may increase its mechanical strength and thermal stability; but it may reduce the dielectric properties, the ability to recover and to transfer hydrophobicity, and increase difficulties in its molding. This research is intended to study vulcanization method and to obtain optimal dose of filler to produce the silicone elastomer as insulating material suitable for high/extra high voltage outdoor insulators in tropical area. The samples used in this research were the silicone elastomer with two different vulcanization methods; they are Room Temperature Vulcanization (RTV) and High Temperature Vulcanization (HTV). The RTV and HTV specimens are subjected to aging under natural tropical climate in open air, particularly in Bandung. This open-air aging test is carried out with two models. First model was without shielding. In this case, the specimen was exposed directly to all of climate factors. The second model was with shielding, in which the samples were protected from the suns UV radiation. In addition, an accelerated aging test was conducted in the laboratory by applying combination of tropical climate factors and electrical field. This accelerated aging test is a screening test. It was used to determine the effects of fillers on the material properties and to identify the quality. A method to measure hydrophobic character has been developed by measuring contact angle of the water drops on the surface of the material. This was used to investigate the changes of silicone elastomer performances, particularly the hydrophobicity of its surface. The change of dielectric properties and its relationship with volume of water absorbed by specimen was determined by Schering bridge, null indicator and Metier balance type AE-240. The measurement was carried out weekly during 120 weeks. Beside that, measurement of the surface conductivity (leakage current), thermal analysis (TGA and TMA), analysis of the chemical structure with ATR-FTIR spectroscopy, and analysis of microstructure of the surface degradation by SEM were also carried out. The results of measurement indicated that both RTV of different filler dose (18-29.2%) and HTV of different filler dose (48-72%) specimens under tropical climate aging in 120 weeks and under artificial aging test in 96 hours were able to maintain their strong hydrophobicity with contact angle of greater than 90 o. The water absorbed by RTV and HTV specimens are 0.08-0.11% and 0.19-0.22%, respectively. Even though the water absorbed is small, it caused the increase of the relative permittivity ( ) of the RTV specimens by 1.02-1.067 times and of the HTV specimens by 1.093-1.83 times of the initial value. The absorbed water also caused the increase of the dissipation factor of RTV samples by 2,55-3,57 and HTV samples by 3,53-26,8 times of the initial value. The measurement results of surface conductivity of both RTV and HTV specimens during aging test did not change significantly. Under voltage of 12 kV, the surface leakage current of the RTV specimens was 6.1-8.36 pA and that of HTV specimen was 6.73-9.49 mA. The thermal analysis of both RTV and HTV specimens showed that they had thermal stability at 240-260 oC and the thermal expansion coefficient (a) was 225-375 mm/m oC. After 120 weeks of aging, however, the thermal properties of RTV containing filler lower or equals to 22,2% indicated the significant increase of a: from 375 to 395 mm/m oC. ATR-FTIR and SEM analysis also showed the change of chemical structure and microstructure on the surface. Chemical structure change was indicated from the change of the absorption peak of C-H, Si-O groups, while the microstructure change was observed from the existence of small tracking and the micro-sized-hole erosions on its surface. From the above-mentioned experiment results and the parameters analysis, it can be concluded that dose of filler of 29.2% for RTV and of 48% for HTV elastomer silicone give optimal performance. Therefore, those two materials can be proposed as insulator materials for high voltage transmission line in tropical area. Thus, the conventional insulator (the porcelain/ceramic and glass), which is heavy and hydrophilic (contact angle of 0 o- 33 o), may be alternatively replaced by the silicone elastomer, which is light and hydrophobic (contact angle of 108 o- 146 o).